Transluminal angioplasty in postsurgical stenosis of the extracranial carotid artery. - Tievsky, A L; Druy, E M; Mardiat, J G (American Journal of Neuroradiology, 1983)
Transluminal angioplasty of the common carotid artery was beneficial in a patient with postendarterectomy recurrent stenosis due to fibrous myointimal hyperplasia. This lesion is the major cause of restenosis within the first 24 postoperative months and has histologic characteristics quite favorable for angioplasty with minimal possibility for embolic complications. Since surgery is a proven procedure with low morbidity/mortality for most patients, the authors believe transluminal angioplasty for carotid restenosis should be limited to surgically inaccessible lesions or patients presenting unacceptable operative risk, as in the case described.